2014
DOI: 10.2174/1876387101407010001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Continuous Solar Adsorption Refrigeration System Driven by Compound Parabolic Concentrator

Abstract: Solar adsorption refrigeration is promising technology especially in the developing countries and remote areas because the system can be driven by solar energy without involving electricity. Therefore, it is technologically possible and socially feasible in the areas where electricity is not enough but solar energy is rather easy to obtain. The conventional system works intermittently and produces cooling only during night. In this article, a solar adsorption refrigerator is presented that produces cooling con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Multi-cycle using zeolite and activated carbon in the upper cycle developed by He et al [50] reported a COP of 0.4. Umair et al [53] simulated the performance of activated carbon fibre/Ethanol for a solar cooling refrigerator. Uddin et al [59] and El-Sharkawy et al [60] tested different 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 versions of chemically modified activated carbons with ethanol.…”
Section: Adsorption Characteristicsmentioning
confidence: 99%
“…Multi-cycle using zeolite and activated carbon in the upper cycle developed by He et al [50] reported a COP of 0.4. Umair et al [53] simulated the performance of activated carbon fibre/Ethanol for a solar cooling refrigerator. Uddin et al [59] and El-Sharkawy et al [60] tested different 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 versions of chemically modified activated carbons with ethanol.…”
Section: Adsorption Characteristicsmentioning
confidence: 99%
“…Umair et al. 14 established a detailed simulation model for a continuous solar adsorption cooling system operated with a parabolic concentrator. They studied the dynamic nature of the system and compared with conventional refrigeration systems.…”
Section: Introductionmentioning
confidence: 99%
“…Umair et al used the compound parabolic concentrator for the evaluation and simulation of a continuous SACS. 38 The choice of a particular configuration depends on different local factors such as climate data, availability of cooling water, the type of collector available, and its initial cost. With the progress of the SACS technology, some silica gel-water adsorption chillers machines have been commercialized successfully on the market.…”
Section: Introductionmentioning
confidence: 99%